Generation and application of monoclonal antibodies against CD4-1 and CD8α for characterizing T cell subsets in grass carp (Ctenopharyngodon idella) - Haokai Chen; Ming Geng; Kang Li; Zhichao Fang; Yating Zhu; Yuqing Yang; Shiqi Tang; Jingfeng Ding; Jiansong Zhang; Jialong Yang; Xiumei Wei (Fish & Shellfish Immunology, 2026)

Strengthening carbon sinks in Tibetan Plateau alpine grasslands over the past four decades - Yuyang Wang; Yaoming Ma; Jingfeng Xiao; Weiqiang Ma; Zhipeng Xie; Zhiyong Ding; Kesi Liu (Agricultural and Forest Meteorology, 2026)

Dietary quercetin enhances T cell immunity and disease resistance in tilapia via modulating antioxidant and inflammatory responses - Haokai Chen; Jingfeng Ding; Yuqing Yang; Shiqi Tang; Qiqi Jiang; Yuying Zheng; Yating Zhu; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

N-acetylcysteine enhances antioxidant capacity and anti-bacterial immunity of T cells in tilapia by regulating KEAP1-NRF2 axis - Kang Li; Shiqi Tang; Jingfeng Ding; Yuqing Yang; Haokai Chen; Qiqi Jiang; Xiumei Wei; Jialong Yang (Aquaculture, 2026)

Bio-electrochemical regulation of sulfur transformations for boosted sulfur-based denitrification and integrated sulfate abatement: Performance and mechanisms - Jingfeng Ding; Gaoming Wu; Dazhi Bai; Bin Yang; Yang Hou; Lecheng Lei; Zhongjian Li (Journal of Environmental Chemical Engineering, 2026)

Dietary ferulic acid boosts the immunity and antioxidant activity of T lymphocytes in Nile tilapia (Oreochromis niloticus) challenged with Aeromonas hydrophila - Jiansong Zhang; Yuqing Yang; Jingwen Chang; Jingfeng Ding; Shiqi Tang; Yishan Lu; Xiumei Wei; Jialong Yang (Fish & Shellfish Immunology, 2026)

Respiration‐Induced Weakening of Land Sink Contributed to the Largest CO 2 Increase in 2024 - Chaoya Dang; Zihua Shi; Josep Peñuelas; Philippe Ciais; Stephen Sitch; Jingfeng Xiao; Xing Li; Yanfeng Ding; Songhan Wang (Global Change Biology, 2026)
In 2024, the global annual growth rate of atmospheric CO 2 (CGR) surged to a record of 3.73 ppm year −1 —the highest since 1959—exceeding the 1.5°C climate threshold for the first time. However, the drivers behind this unprecedented rise remain poorly understood. Here, we employed a machine‐learning approach integrating satellite‐derived gross primary productivity (GPP) and climatic data to estimate the 2024 land sink (S LAND ) at approximately 2.21 ± 0.25 GtC year −1 , which had a striking decline of 1.01 GtC year −1 compared to the 2014–2023 average. The reduction in S LAND , most pronounced in tropical regions, contributed ~50% to the 2024 CGR increase—a larger impact than that of fossil fuel emissions or ocean sinks. Moreover, using partial least squares structural equation modelling, we further explained the underlying mechanism for the reduction of the S LAND in 2024, which was caused by hotter and drier conditions leading to a larger increase in respiration than photosynthesis. Our findings underscore the urgent need to investigate the mechanisms behind the declining carbon sink amid persistent global greening. These results challenge previous assumptions about the long‐term stability of the terrestrial carbon sink and highlight society's growing dependence on adaptive strategies to mitigate climate warming.

Dual-mode regulation of cyclohexylamine biodegradation by dissolved oxygen: Metabolic trade-offs and community stability mechanisms - Cheng Qiu; Jingfeng Ding; Minwen Guo; Can Chen; Wenwu Zhang; Bin Yang; Yang Hou; Zhongjian Li (Journal of Water Process Engineering, 2026)

Enhanced T-cell activation and effector functions contribute to disease resistance in Streptococcus agalactiae-resistant tilapia - Ming Geng; Jingfeng Ding; Jun Xiao; Liting Chen; Jiansong Zhang; Kang Li; Jie Cheng; Yi Cao; Jialong Yang; Xiumei Wei (Aquaculture, 2026)

Spider web-inspired ZIF@PPy conductive networks for efficient flow-electrode capacitive desalination of high-salinity antibiotic wastewater - Huachun Pan; Jingfeng Ding; Shuangwei Chen; Zhikang Li; Zhikan Yao; Chen Sun; Yang Hou; Zhongjian Li; Lecheng Lei; Bin Yang (Chemical Engineering Journal, 2025)

Operation characteristics based on a novel performance model based on capacity utilization rate of a variable refrigerant flow air conditioning system - Hansong Xiao; Shurong Liu; Yunxiao Ding; Chunyuan Zheng; Bing Luo; Heng Niu; Jingfeng Shi; Baolong Wang; Qiang Song; Wenxing Shi (Energy and Buildings, 2023)

Biological control efficacy of Bacillus licheniformis HG03 against soft rot disease of postharvest peach - Xiaoli Wang; Jingfeng Zhu; Huan Wei; Zhipeng Ding; Xiran Li; Zao Liu; Hongbao Wang; Yunpeng Wang (Food Control, 2023)